NEW CHALLENGES FOR THE LEGAL EDUCATION IN LATVIA - Grasis, Janis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The Cabinet of Ministers of the Republic of Latvia adopted Regulation No. 46 “Procedures for the National Uniform Professional Legal Qualification Examination” on January 15, 2019. These rules will apply to students who started studies in the course of the professional master's study programme at the autumn semester of 2019; therefore, the first exam will be in 2021. The qualification examination will have the following parts: (1) the theoretical part in which detailed answers to 15 questions are provided in writing; (2) the practical part in which five practical tasks (case -studies) are dealt with in writing. Novelty of the research: this is one of the newest academic research concerning the mentioned examination which is something new for Latvian legal education, trying to make comparision with analogous Uniform Examination in Germany. The research aim is to analyse critically the new regulations and how will it affect existing master programmes of law in the universities of the Republic of Latvia. Descriptive, analytical and deductive-inductive research methods are used. Legal acts, policy planning documents and different reports were reviewed and analyzed, and subsequently conclusions and recommendations were made. On the one hand the introduction of the mentioned examination could contribute to increasing motivation of students, to acquiring deeper and more sustainable knowledge in law study programmes, which can be assessed positively. However, it is not clear what the criteria are, the content of what the requirements will be for the methodology for evaluating the National Uniform Professional Legal Qualification Examination, which is approved by the commission itself. This could be a risk element for transparency and uniform understanding during the development of examination questions and in the evaluation process of examination answers.